[tex](x+5)^2=4(y+2)[/tex]
the equation for a parabola with focus (h, k+p) and directrix y=k-p is
[tex](x-h)^2=4p(y-k)[/tex]
so using your directrix y=-3, and knowing directrix is y=k-p, you have
-3=k-p.
similarly, knowing the focus is defined by (h,k+p) and your focus is (-5,-1)
you have the equation -1=k+p.
you now have a system of equations
[tex]-3=k-p \\ -1=k+p[/tex]
which you can solve using any method, I will use elimination.
adding down
[tex]-4=2k \\ -2=k[/tex]
you now have k and can find p using either equation.
[tex]-3=k-p \\ -3=-2-p \\ -1=-p \\ 1=p[/tex].
now you plug those in, getting the answer
[tex](x+5)^2=4(y+2)[/tex]